The thrombopoietin receptor P106L mutation functionally separates receptor signaling activity from thrombopoietin homeostasis - Stockklausner, Clemens; Klotter, Anne-Christine; Dickemann, Nicole; Kuhlee, Isabelle Nadine; Duffert, Christin; Kerber, Carolin; Gehring, Niels H.; Kulozik, Andreas (Blood, 2015)
Key Points. The c-Mpl activity in downstream signaling and in platelet homeostasis can be functionally separated.The c-Mpl platelet homeostasis depends on corr